Tinjauan Performansi Bubut Doll LT13 Terhadap Penyimpangan Kebulatan Benda Kerja - Ariyanto Ariyanto; Husman Husman; Yuli Dharta (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
The industry manufacture with high quality and able to pruduce the workpicece with high quality In industry manufacture are very necessary. The use of high quality machines should be supported by the ability to operate and the ability to perform maintenance, this ability is useful to maintain the condition of the machine in order to produce good quality workpieces. Politeknik Manufaktur Negeri Bangka Belitung has several high quality machine tools, one type of machine tools usually use is lathe machine doall LT13 with total have six units. this machine Used to support education and to produce spare parts. Doall LT13 lathes have been used for 22 years, during that period there may be deviation of machine geometry, deviations that occur can lead to decreased quality of the resulting workpiece. This study aims to determine the feasibility of the machine by measuring the roundness of the spicemen of the process of turning, the roundness of the specimen is analyzed by using the minimum circle method. From the roundness testing performed on the doall lt 13 the result? that can be achieved as follows 0,082 mm at lathe number 8, 0,073 mm at lathe number 5, 0,057 mm at lathe number 7, 0,051 mm at lathe? number 2, 0,048 mm at lathe number 6 and 0,046 mm at lathe number 3.